2015
DOI: 10.17016/feds.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Every Little Bit Counts: The Impact of High-speed Internet on the Transition to College

Abstract: This paper investigates the effects of high-speed Internet on students' college application decisions. We link the diffusion of zip code-level residential broadband Internet to millions of PSAT and SAT takers' college testing and application outcomes and find that students with access to high-speed Internet in their junior year of high school perform better on the SAT and apply to a higher number and more expansive set of colleges. Effects appear to be concentrated among higher-SES students, indicating that wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Similarly, timing of disclosure has been shown to impact consumer responsiveness (Della Vigna and Pollet ), and whether a September 12 release date, which coincided with the beginning of the school year, was timed properly to garner enough attention from the media or students is an open question. Finally, even if students have preferences for the metrics presented on the Scorecard, they may lack awareness of the Scorecard or not have enough time to access these data, which may be particularly true for traditionally underserved students (e.g., Dettling, Goodman, and Smith Forthcoming; Haskins, Holzer, and Lerman ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, timing of disclosure has been shown to impact consumer responsiveness (Della Vigna and Pollet ), and whether a September 12 release date, which coincided with the beginning of the school year, was timed properly to garner enough attention from the media or students is an open question. Finally, even if students have preferences for the metrics presented on the Scorecard, they may lack awareness of the Scorecard or not have enough time to access these data, which may be particularly true for traditionally underserved students (e.g., Dettling, Goodman, and Smith Forthcoming; Haskins, Holzer, and Lerman ).…”
Section: Introductionmentioning
confidence: 99%
“…While the introduction of online and telephone-based application processes for Unemployment Insurance (UI) has not been shown to significantly affect UI take-up or change the composition of UI applicants (Ebenstein & Stange, 2010), the increased availability of electronic tax filing increases participation in the Earned Income Tax Credit (EITC) (Kopczuk & Pop Eleches, 2007). Other work has found that high-speed internet access increases college preparation and application activity for high-SES high school students (Dettling et al, 2018), and increases labor supply among married women (Dettling, 2016).…”
Section: Prior Literaturementioning
confidence: 99%
“…The count of internet providers captures the extent of variation in the supply of high-speed internet access, which was the main constraint on access during the time frame of our analysis. 6 Other research has also demonstrated the count of internet providers as an effective measure of internet access (Dettling et al, 2018;Iyengar & Westwood, 2015). The FCC Form 477 collects records of the number of high-speed internet service providers with over 250 high-speed residential lines at the zip code or county level, depending on the year.…”
Section: Measures Of Connectivitymentioning
confidence: 99%
See 2 more Smart Citations